Perda dentária e controle glicêmico de idosos com diabetes do tipo 2 - Barroso Júnior, Jorge Brandão (2013)
Introduction: Some studies had shown that the periodontal treatment can interfere with the glycemic control of diabetes patients. Thus, it can be hypothesized that in the absence of a periodontal infection, as in an edentulous or healthy periodontal patient, the glycemic control of type 2 diabetes patients can be improved. Objectives: The aim of this cross-sectional study was to compare the glycemic control of type 2 diabetes edentulous and dentate patients presenting or not periodontal diseases. Methods: There were selected type 2 diabetics according to the following criteria: they must be non-smokers, aging 60 years or more and being under therapy with hypoglycemics. Subjects were assigned to two groups based on their respective dental condition: edentulous (DESD, n=124) and dentate (DENT, n=65) The glycemic control was analyzed by fasting serum glucose (FSG). Results: It was found significant differences (p<0.05*) for mean GJ between groups DESD (144,9 ± 66,9 mg/dL) and DENT (120,4 ± 38,0 mg/dL). But when the DENT group was divided according to the presence of periodontitis (DENT-P; GJ=126,7 ± 44,6 mg/dL) or not (DENT-A; GJ= 117,4 ± 34,2 mg/dL), this difference was observed only between DESD and DENT-A. It was also observed that DESD group showed higher risk to present hyperglycemia when analyzed through two GJ cutoffs: GJ ≥ 126 mg/dL, Odds ratio (OR) = 2,01 (CI 95%=1,08 - 3,73) and GJ ≥ 170 mg/dL, OR = 2,47 (CI 95%=1,07 - 5,76). Conclusions: Edentulous type 2 diabetes patients presented higher glycemic levels than dentate ones. But, in these patients, the presence of periodontal diseases, along with other non-investigated factors could interfere with their glycemic control.